The Effect of Positive Affirmation Therapy on Anxiety Levels in Mothers Facing Menopause in the South City Community Health Center Work Area - Nurdiyani Aliwu; Ika Wulansari; Mihrawaty S. Antu (Universitas Muhammadiyah Palu, 2026)
Menopause is a natural phase in a woman's life that is often accompanied by physical and psychological changes, one of which is anxiety. Anxiety that is not managed properly can negatively impact the quality of life of menopausal women. One non-pharmacological effort that can be done to reduce anxiety is positive affirmation therapy. This study aims to determine the effect of positive affirmation therapy on maternal anxiety levels in facing menopause in the South Kota Community Health Center area. This study used a quantitative method with a quasi-experimental design through a pretest–posttest control group design approach. The study population amounted to 83 people with a sample of 36 respondents consisting of 18 respondents in the intervention group and 18 respondents in the control group, selected using a purposive sampling technique. The instrument used was the Hamilton Anxiety Rating Scale (HARS). Data analysis was performed using the Wilcoxon test to determine the effect of anxiety levels before and after the administration of positive affirmation therapy. The results showed a significant decrease in anxiety levels in the intervention group after being given positive affirmation therapy compared to the control group. The statistical test results showed a p-value <0.05, indicating that positive affirmation therapy significantly reduced maternal anxiety levels during menopause. The study concluded that positive affirmation therapy significantly reduced anxiety levels in menopausal mothers. This therapy is recommended as a simple, safe, and effective non-pharmacological intervention to help mothers cope with menopause.